The complete chloroplast genome of Scutellaria tsinyunensis (Lamiaceae), an endemic species from China. Issue 3 (2nd July 2020) - Liu, Xiangning; Zuo, Youwei; Lin, Le; Li, Wenqiao; Wang, Qian; Deng, Hongping
Abstract: Scutellaria tsinyunensis (Lamiaceae) is an endangered species endemic to Mt. Jinyun of Chongqing, China. In this study, the complete chloroplast (cp) genome of S. tsinyunensis was sequenced and characterized. The cp genome is 152, 066 bp in length with a typical quadripartite structure, containing a pair of inverted repeats (IRs) of 25, 223 bp separated by a large single-copy (LSC) region and a small single-copy (SSC) region of 84, 096 bp and 17, 524 bp, respectively. The whole cp genome contains 130 genes, including 86 protein-coding genes, 36 tRNA genes, and eight rRNA genes. The overall GC content of the circular genome is 38.4%, whereas the corresponding values in LSC, SSC, and IR regions are 36.4, 32.6, and 43.6%, respectively. The phylogenetic analysis based on the complete cp genomes of the Lamiaceae family indicated that S. tsinyunensis was closely related to S. insignis .